Palangka Raya City’s Strategy to Overcome Congestion in the School Area - Saphira, Bella; Tulis, Riamona Sadelman; Setiawan, Ferry; Ayu, Katriani Puspita; Sahay , Marvy F.A. (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
Traffic congestion in the school environment, especially during school departure and return hours, is a significant problem. This study aims to identify the causes of traffic congestion and evaluate strategies that can be applied in overcoming these problems. The research method used is descriptive with a qualitative approach, using observation, interviews, and documentation as data collection techniques. SWOT analysis was conducted to assess the internal and external factors of the applied strategy. The results showed that congestion is caused by various factors, including student shuttle activities, indiscriminate vehicle parking, limited parking lots, crossing the road, and street vendors selling around the school. The Transportation Agency's efforts include traffic regulation by officers in the field and appeals to schools and parents. However, there are weaknesses in terms of limited human resources and traffic infrastructure. The conclusion of this study is the need to optimize existing strategies, including additional personnel, provision of “kiss and ride” parking facilities, and procurement of more adequate traffic signs. In addition, enforcement of traffic rules and socialization to the community need to be improved in order to maintain smooth traffic flow and improve safety around schools.